Cameroon's forests and people: collection of publications, maps, pictures, hyperlinks and references (Center for International Forestry Research, 2003)
This CD-ROM strives to be a state of the art compilation of key documents on Cameroon's forests in the course of the last two decades--forests that have been subject to numerous reforms concerning management, conservation and forest policy.